Public Tenders for Music Teachers in the South of Brazil (Asian Education Studies, 2019)
This article presents the research that investigated the performance of open procedure for music teachers in municipal schools in Rio Grande do Sul, (a) state in the south of Brazil. The methodology included Internet research and, for data analysis, Content Analysis. The theoretical reference was based on concepts of Musical Education marked by the Policy Cycle Approach. Considering the 2008 mid-2017 time cut-off, sixty (public) notices were identified for the hiring of music teachers. Out of the 497 municipalities that make up the state, 133 conducted Employment tests. Still, it is understood that there are great challenges for the presence of music in state schools.